Karmelici trzewiczkowi prowincji wielkopolskiej w XVII-XIX wieku - Kloskowski, Grzegorz (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The inspiration for writing this article was “A small chronicle of the residence of the Carmelites of the Ancient Observance in Poznań”. The following work is the first study based on sources concerning directly the monks from the province of Great Poland. The presented data refl ect only the information included in the given sources and publications and they are the basis for the further study on this monastic family. The study focuses on the Carmelites of the Ancient Observance in the Great Poland Province from 1686, the year when they came into their own, to the dissoluton of the orders in the 19th century. The article is not the catalogue of the monks; it only shows the basic biographical details, which should be confronted with other sources. This source study does not follow the current standards either; it is only the compilation of a few sources. In this way we can gain more details about particular monks. These are not probably all monks of this province, and the subsequent manuscripts and publications will show new characters.